PENERAPAN NILAI-NILAI PANCASILA DALAM KEBIJAKAN EKONOMI DI KABUPATEN TEGAL 2009-2014 - EKO EDDYA SUPRIYANTO, EKO EDDYA SUPRIYANTO (Program Magister Ilmu Politik, Universitas Diponegoro, 2013)
Pancasila as the national ideology is a political agreement as the FoundingFather of Indonesia state Funded. Pancasila as the state becomes the foundation for allareas, not least of Economic Policy. But international competition through globalization is achallenge for family economic containing the values of Pancasila to expand its sovereignty.The purpose of this study was to determine the Pancasila in the era ofglobalization and the implementation of Pancasila values in economic policy in Tegalregency views of the Medium Term Development Plan 2009-2014.This study uses descriptive analytical research on Pancasila was conducted inTegal regency by analyzing economic policy Tegal regency with the values of Pancasila,seen from the Medium Term Development Plan 2009-2014 Tegal regency.The existence of Pancasila values in Tegal regency very obvious when viewedfrom the vision and mission, as well as Medium Term Development Plan 2009-2014. But inthe translation program implementation vision and mission Tegal has not done optimally.Keywords: Pancasila values, Globalization, Economic Pancasila.